Perlindungan Hukum Klaim Asuransi Pemegang Polis Asuransi - Fina Rohmatika (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Life insurance has become integral to individual and family finances in the modern era, providing financial protection and peace of mind. Life insurance claims involve complexities that require in-depth understanding from both the policyholder and the insurance company. Legal protection in insurance claims is important to ensure policyholder rights are protected. This article investigates legal protection for life insurance policyholders during the claims process, analyzing regulations, dispute resolution mechanisms, and how legal protection ensures policyholder rights are safeguarded. The research method uses a juridical-normative approach with literature study, applying analytical descriptive analysis. The results illustrate the importance of understanding statutory provisions, consumer protection, and dispute resolution.